Drug Brand Response and Its Impact on Compliance and Efficacy in Depression Patients - Li, Mingming; Cai, Jian; Zhang, Ping; Fei, Chunhua; Xu, Feng (Frontiers in Pharmacology, 2017)
Introduction:Patient’s response to drug brand is a comprehensive physiological and psychological effect which might impact the compliance and efficacy of drugs. Whether the therapeutic outcome altered on patients with brand response after they experience drug switch is not clear. Methods:459 outpatients with mild-to-moderate depression were divided into the imported (joint venture) drug group and the domestic drug group according to their current drug application. Two groups of patients were assessed by drug brand preference questionnaire and medication compliance questionnaire. Patients with brand preference in imported (joint venture) drugs group received rational use of limited medical resource and pharmacoeconomics education, and then switched with domestic drug for 8 weeks. Safety and efficacy were evaluated both before and after the drug switch. Result:Overall, there were 27% of patients in imported drug group and 35% of patients in domestic drug group have brand response, respectively. About 2/3 patients in both groups showed low or no brand response. The compliance was similar in both groups with no significant difference (6.04±2.08 vs 4.74±2.13, respectively, P>0.05). The efficacy of imported drug group was significantly better than of the domestic drug group. Correlation analysis showed that in imported (joint venture) drugs group, medication compliance was closely related with brand response, but negatively correlated with age and duration. In domestic drugs group, medication compliance was independent of brand response, but closely related with education, age, and duration. After drug switch with domestic drug on patients with brand response, patients continued to maintain good antidepressant effect, and no severe adverse reaction occurred. Conclusion:The results suggested that domestic drugs switch might be feasible for patients using imported drugs with brand response, while providing patients with rational use of drug education and psychological support. The medical staff should focus on medication education to help patients make better use of limited medical resources.